Budaya dan Agama Sebagai Sistem Simbolik: Studi Interaksi Komunikasi Dakwah Peziarah Makam Syekh Quro dalam Perspektif Clifford Geertz - Upi Zahra; Saepullah; Nazwa Adelia Putri (Kopertais Wilayah I DKI Jakarta dan Banten, 2026)
This research aims to reveal the forms of da'wah communication interaction among pilgrims at the Tomb of Syekh Quro in Karawang, and to analyze how culture and religion function as a symbolic system from the perspective of Clifford Geertz’s interpretive theory. The research employs a qualitative approach with an interpretive ethnographic design, involving pilgrims, caretakers, religious figures, tomb managers, and village officials as informants selected through purposive and snowball sampling. Data were collected through in-depth interviews, participant observation, and documentation. The findings show that da'wah communication interaction manifests in the form of congregational prayers, recitation of tahlil and manaqib, oral advice, and nonverbal symbols such as gestures of respect and the arrangement of sacred space. All of these frame the pilgrims’ spiritual experience and reinforce the value of tawhid. Culture and religion appear as a layered symbolic system through the Sabtuan night tradition, narratives about Syekh Quro’s piety, and the presence of physical artifacts such as the tomb, mosque, and trees believed to bring blessings. Together, these form patterns of collective meaning and the community’s religious identity. The study concludes that the Tomb of Syekh Quro functions as a culturally based da'wah space, where local symbols become an effective medium for spreading Islam amid the dynamics of religious tourism and social change. These findings contribute to the development of da'wah communication studies and religious studies by demonstrating the relevance of the interpretive approach in reading pilgrimage practices as living cultural texts.